Ecsiccatae “Lichenes Selecti Germanici” of G.W.Körber in the Herbarium of V.N.Karazin Kharkіv National University (CWU) - Громакова, А. Б.; Гамуля, Ю. Г. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The information on ecsiccatae collection «Lichenes Selecti Germanici» of G.W.Körber that is stored in the Herbarium of V.N.Karazin Kharkіv National University (CWU) is presented in the article. The collection has been catalogued and the list of ecsiccatae has been compiled, which includes 101 samples. 10 of these samples belong to types material. The lectotype of Coniangium krempelhuberi (Körb.) A. Massal. has been selected and isotypes have been found for Biatora diaphana Körb., Buellia occulta Körb., Coniangium glaucofuscum Körb., Lecanora complanata Körb., Lecidea superba Körb., Psorotichia pelodes Körb. ex Stein., Ramalina carpatica Körb. and Steinia luridescens Körb. species.